2017
DOI: 10.1097/jom.0000000000001123
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Function in Latino Farmworkers Over 2 Years

Abstract: Objective We compared patterns of olfactory function over two years in pesticide-exposed male Latino farmworkers and male Latino workers in industries without pesticide exposure. Methods At five points over two years, workers completed tests of odor threshold (16 concentrations of n-butanol) using a well-established methodology. Tests at two or more time points were completed by 156 farmworkers and 118 non-farmworkers. Results Farmworkers required significantly higher odorant concentrations at Contact 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The best evidence to date comes from a recent study (Quandt et al. 2016, 2017) that compared the sense of smell of 304 Latino farmworkers and 247 non-farmworkers in North Carolina, 18–70 y of age (78% younger than 45 y of age). This study found that farmworkers were not significantly different from controls in smell identification, but they had higher olfactory thresholds that persisted throughout a 2-y follow-up period (Quandt et al.…”
Section: Discussionmentioning
confidence: 99%
“…The best evidence to date comes from a recent study (Quandt et al. 2016, 2017) that compared the sense of smell of 304 Latino farmworkers and 247 non-farmworkers in North Carolina, 18–70 y of age (78% younger than 45 y of age). This study found that farmworkers were not significantly different from controls in smell identification, but they had higher olfactory thresholds that persisted throughout a 2-y follow-up period (Quandt et al.…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory and hearing loss were studied by Quandt et al 33 and França et al 8 , respectively. In a study of Latino workers exposed to pesticides in the United States, Quandt et al 33 found that pesticides can significantly affect olfactory function even when inhaled at low doses. The study also found that olfactory impairment occurs earlier than other symptoms of neurodegenerative diseases such as Parkinson’s.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies measured the changes in olfactory function due to occupational exposure to air pollution (e.g., metals and volatile organic compounds VOCs), among which 16 assessed the long-term exposure. Twelve studies used both the odor threshold test and the odor identi cation test [24][25][26][27][28][29][30][31][32][33], and three studies found no decline in the olfactory function measured by either test type (25%) [22][23][24]. Many studies assessed participants' exposure to volatile organic compounds (VOCs) (e.g., phenyl-ethyl alcohol, n-butanol, styrene, and formaldehyde), and these tests tend to have good reliability and validity.…”
Section: Odor Threshold Testsmentioning
confidence: 99%